Autologous Cytokine-Induced Killer Cell Immunotherapy Enhances Chemotherapy Efficacy against Multidrug-Resistant Tuberculosis - Peijun Tang; Xingnian Chen; Junchi Xu; Yunlong Hu; Zhijian Ye; Xiafang Wang; Yumei Xiao; Xinghua Shen; Jianping Zhang; Yanjun Feng; Cuilin Shi; Xin Yu; et al. (Journal of Immunology Research)
Objective. Multidrug-resistant tuberculosis (MDR-TB) causes persistent infection and challenges tuberculosis control worldwide. T cell-mediated immunity plays a critical role in controlling Mycobacterium tuberculosis (Mtb) infection, and therefore, enhancing Mtb-specific T cell immune responses represents a promising therapeutic strategy against TB. Cytokine-induced killer (CIK) immunotherapy is based on autologous infusion of in vitro expanded bulk T cells, which include both pathogen-specific and nonspecific T cells from patient peripheral blood mononuclear cells (PBMC) into TB patients. Preclinical mouse studies have shown that the adoptive T cell therapy inhibited Mtb infection. However, the efficacy of CIK immunotherapy in the treatment of MDR-TB infection has not been evaluated in clinical trials. Methods. We performed a retrospective study of MDR-TB patients who received CIK immunotherapy in combination with anti-TB chemotherapy and those who had standard chemotherapy. Results. Our results showed that CIK immunotherapy in combination with anti-TB chemotherapy treatment increased the conversion rate of sputum smear and Mtb culture, alleviated symptoms, improved lesion absorption, and increased recovery. The kinetics of serology and immunology index monitoring data showed good safety profiles for the CIK treatment. Conclusion. Our study has provided strong evidence that CIK immunotherapy in combination with anti-TB chemotherapy is beneficial for MDR-TB patients. A multicenter clinical trial is warranted to evaluate CIK as a new immune therapy for MDR-TB.